PENGARUH LAMA PENGASAPAN TERHADAP SIFAT FISIK DAN MEKANIK KAYU LABAN Vitex pubescens Vahl DAN AKASIA Acacia mangium Willd - Penus, .; Diba, Farah; Sisillia, Lolyta (Universitas Tanjungpura, 2017)
Handicraft from West Borneo consists of Mandau, statue, wall decoration and others were made from Ulin wood (Euzideroxylon zwageri).Â Now the supply of Ulin wood is decreasing and make the craftsmen used another raw material by using Laban wood (Vitex pubescens Vahl) and Acacia wood (Acacia mangium Willd). This wood has lower quality than Ulin wood. The craftsman used traditional smoke wood method to increase the physical and mechanical properties of wood. This method takes a long time and uneven colors. The objectives of the study were to improve the physical and mechanical properties of Laban and Acacia wood used the modern smoke process with various time of smoking. Preparation of test samples of physical and mechanical properties refer to British Standard No. 373 year 1957, with 3 (three) repetitions. Sample for water and wood density test was measured 2 cm x 2 cm x 2 cm, sample for wood dimension and color change was 4 cm x 2 cm x 2 cm, sample for hardness of wood was 6 cm x 2 cm x 2 cm and sample for mechanic crush strength was 8 cm x 2 cm x 2 cm. Smoking time used were 12 hour, 24 hour and 36 hour. Result of the research showed that smoking technique increase the physical and mechanical properties of Laban and Acacia wood. The best time for smoking wood to increase the physical and mechanical properties of Laban wood was achieved at 24 hours, meanwhile in Acacia wood was at 36 hours. Keywords: Acacia wood, handicraft, Laban wood, smoking wood, time exposure